Cell Therapy With TILs: Training and Taming T Cells to Fight Cancer - Kumar, Amrendra; Watkins, Reese; Vilgelm, Anna E. (Frontiers in Immunology, 2021)
The rationale behind cancer immunotherapy is based on the unequivocal demonstration that the immune system plays an important role in limiting cancer initiation and progression. This revolutionary treatment utilizes a patient’s own immune cells to find and eliminate tumor cells, however, donor immune cells can also be employed in some cases. Here, we focus on T lymphocyte (T cell)-based cancer immunotherapies that have gained significant attention after initial discoveries that graft-versus-tumor responses were mediated by T cells. Accumulating knowledge of T cell development and function coupled with advancements in genetics and data science has enabled the use of a patient’s own (autologous) T cells for adoptive cellular immunotherapies (TIL ACTs). In TIL ACT, tumor-infiltrating lymphocytes (TILs) are collected from resected tumor material, enhanced and expanded ex-vivo, and delivered back to the patient as therapeutic agents. ACT with TILs has been shown to cause objective tumor regression in several types of cancers including melanoma, cervical squamous cell carcinoma, and cholangiocarcinoma. In this review, we provide a brief history of TIL ACT and discuss the current state of TIL ACT clinical development in solid tumors. We also discuss the niche of TIL ACT in the current cancer therapy landscape and potential strategies for patient selection.